The Management of Situational Prevention Knowledge in Iran’s Police - Ali Afrasiabi; Abolfath Khaleghi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2014)
In the management of crime prevention knowledge, scientific sources and reports on administrative situational prevention projects are collected, organized and divided into portions. The question which is risen is why the management of situational Prevention knowledge is necessary in Iran’s police and how is this knowledge managed. Iran’s Police is a governmental, hierarchical and concentrated Organization. Network based and horizontal relationships are limited in such organizations, and Initiative in carrying out administrative duties is replaced by routine activities. In the absence of knowledge management mechanism, police officers are unwilling to exchange experiences. Requirement based on increasing of efficiency is another reason which doubles the necessity of knowledge management in Iran’s police. Due to the management of prevention knowledge, in the first step, police activities shall be executed in the framework of process identified in this paper. In the next step, executive branches of police force send reports on successful projects to the center of applicable studies which is in the office of prevention police in order to be investigated and displayed on the website, afterward. Collection and displaying the crime prevention studies on this website alongside reports of successful projects makes the cycle of knowledge Management. Continuation of this cycle leads to activation of knowledge in police organization.